2010
DOI: 10.1111/j.1467-968x.2010.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

The roles of phonology and analogy In Old English high vowel deletion

Abstract: The problem under consideration is the exact nature of the application of High Vowel Deletion (HVD) in Old English. As discussed in §1, according to what has come to be the most prevalent view, a form such as nom.acc.pl. hēafdu‘heads’ in Late West Saxon, from earlier *hēafudu, is the phonologically regular result of the application of HVD. In §2 a recent alternative explanation is discussed, whereby *hēafudu should have produced *hēafd, which was subsequently reformed to hēafdu in West Saxon on the basis of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…We have seen that a number of theorists have attempted to describe syncopated hēafdu under the assumption that this is the phonologically regular form of this word. Much recent work, however, has shown that the oldest form of this word is most likely hēafudu , with preservation of both final vowels (Bermúdez‐Otero : 32‐4; Fulk ). The attestations of * hēafudu show considerable variation, with hēafudu , hēafdu , and hēafod all occurring (with further variation between u and o , and sometimes occurring with a distinct ending ‐a ).…”
Section: Lack Of Original Syncope Of Hēafudumentioning
confidence: 95%
See 3 more Smart Citations
“…We have seen that a number of theorists have attempted to describe syncopated hēafdu under the assumption that this is the phonologically regular form of this word. Much recent work, however, has shown that the oldest form of this word is most likely hēafudu , with preservation of both final vowels (Bermúdez‐Otero : 32‐4; Fulk ). The attestations of * hēafudu show considerable variation, with hēafudu , hēafdu , and hēafod all occurring (with further variation between u and o , and sometimes occurring with a distinct ending ‐a ).…”
Section: Lack Of Original Syncope Of Hēafudumentioning
confidence: 95%
“…The importance of foot structure in conditioning the loss of high vowels in Old English can be simply illustrated by the nom.‐acc.pl endings of neuter a –stem nouns (Hogg [] 2011 : 220). The pre‐OE form of this ending was * ‐u , and is preserved as such after initial light syllables: fat–u ‘cups’ < * fat–u .…”
Section: The Background Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Ringe argues that the consensus view that syncope and apocope of unchecked *ĭ and *ŭ after stressed heavy syllables apply at the same time (Campbell 1962;Hogg 1992;Fulk 2010) is incorrect, and that syncope in fact preceded shortening of word-internal unstressed long vowels, which preceded apocope ( §6.8). This predicts that the outcomes of regular sound change applied to prehistoric *hēaβudu "heads" should be hēafd, *mae riþu "fame" should be mae rþ, etc.…”
Section: Phonology and Morphologymentioning
confidence: 99%